Effect of Hardness in 3 ppt of Water Salinity on growth and survival rates of Barb Fish (Barbus conhonius Hamilton-Buchanan) - Nirmala, Kukuh; Wulandari, R.; Djokosetiyanto, D. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
This study was conducted to determine the effect of hardness on growth and survival rate of barb fish (Barbus conchonius Hamilton-Buchanan) reared in the 3 ppt of water salinity. Fish were reared in three different hardnesses, i.e., 54, 72, and 90 mg/L CaCO3 for 30 days. The results of study showed that fish reared in water hardness of 72 mg/L CaCO3 had higher daily growth rate (1.15%) compared with other treatments. Daily growth rate of fish reared in water hardness of 54 and 90 mg/L CaCO3 were 0.76 and 0.37%, respectively. There was no effect of hardness on survival rate of barb fish. Keywords: barb fish, Barbus conchonius, hardness, salinity ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh kesadahan yang berbeda terhadap laju pertumbuhan dan tingkat kelangsungan hidup ikan barbir (Barbus conchonius Hamilton-Buchanan) yang dipelihara pada air bersalinitas 3 ppt. Ikan dipelihara dalam 3 tingkat kesadahan yang berbeda, yaitu 54 mg/L CaCO3, 72 mg/L CaCO3, dan 90 mg/L CaCO3 selama 30 hari. Hasil penelitian menunjukkan bahwa laju perumbuhan harian tertinggi diperoleh pada ikan yang dipelihara pada kesadahan 72 mg/L CaCO3 (1,15%) dibandingkan dengan perlakuan lainnya. Laju pertumbuhan harian ikan yang dipelihara pada kesadahan 54 dan 90 mg/L CaCO3 masing-masing mencapai 0,76% dan 0,37%. Kelangsungan hidup ikan barb tidak dipengaruhi oleh kesadahan. Kata kunci: ikan barbir, Barbus conchonius, kesadahan, salinitas